English education master students' perceptions on their professional identity as future EFL teachers - Wijaya, Kristian Florensio (Journal of English Language and Pedagogy, 2021)
Abstract: Dealing with ever-changing globalized ELT enterprises, it is crucially indispensable for future EFL teachers to continually construct, nurture, and amplify a higher degree of professional identity to be not only deemed as competent but also compassionate educators. The establishment of professional identity has an intertwining rapport with the potential second language learning outcomes obtained by learners. Jointly with this basic educational tenet, it can be conjectured that EFL teachers instilling a higher degree of professional identity are more capable of promoting more enjoyable, holistic, and safer teaching-learning enterprises for multiverse learners. While EFL teachers inculcating a lower level of professional identity encounter more frustrating and energy-draining teaching journeys due to the ineptitude of positioning more precise professional identity in their working places. This study was manifested qualitatively by lending further support from 5 open-ended narrative inquiry questions probing more exhaustively into English education master students’ perceptions on their professional identity as future EFL teachers. To support this data gathering process, 2 English education master students batch 2018 and 2020, Sanata Dharma University were invited to record their responses in accord with their teaching experiences as well as aspirations to be more highly professional future EFL educators. The results unfolded that a higher degree of professional identity would potentially allow prospective EFL educators to establish a more positive rapport with educational stakeholders and transform into more supportive learning facilitators. Based on the above-mentioned results, worldwide educational institutions must address insistent external supports to foster their professional identity construction gradually over time. Keywords: master students, narrative inquiry, professional identity